OCUPAÇÃO AMBIENTAL DE ANUROS EM UMA POÇA TEMPORÁRIA NUM FRAGMENTO DE MATA ATLÂNTICA DE PERNAMBUCO - Santos, Ednilza M.; Vasconcelos, Simão D. (Revista Nordestina de Zoologia, 2011)
This study was carried out in a temporary pond, at Tapacurá Ecological Station, São Lourenço da Mata, Pernambuco, Brazil, and aimed at characterizing the environmental occupation and frequency of occurrence of amphibian anurans. Nocturnal and diurnal observations were performed monthly between September/1999 and August/2000. Twenty-five species from four families were recorded in the pond: Bufonidae (1), Hylidae (13), Leptodactylidae (6), Leuperidae (2), Microhylidae (2) e Ranidae (1). Six micro-environments were occupied, from which the emergin plants were the most commonly occupied. There was habitat partition, especially between Hylidae that occupied emerging vegetation in the border and the middle of the pond.